Harta Waris yang Dijual sebelum Pembagian - Shadad Aldiansyah; Kamaliah R; Abdullah Sani (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Inheritance property is one of the important aspects of Islamic law that must be divided in accordance with the provisions of faraidh. However, there is often a practice of selling inherited property before the faraidh division is carried out, which raises the potential for conflict among the heirs. This study aims to analyze the views of the Indonesian Ulema Council (MUI) on the phenomenon, focusing on aspects of Islamic law and ethics in the management of inherited property. The research method used is a qualitative approach with literature studies and interviews. The main sources of this research include MUI fatwas, fiqh books, and interviews with scholars and Islamic law practitioners. The results show that the sale of inherited property before the faraidh division can be justified under certain conditions, such as the agreement of all heirs who are baligh and rational, and does not harm the entitled parties. However, MUI emphasizes the importance of prioritizing the principles of justice and deliberation in the management of inherited property. This study concludes that the sale of inherited property before difaraidh requires caution and compliance with Islamic law, so as not to violate the rights of other heirs. The recommendations given are strengthening public literacy regarding faraidh law and enforcing sharia-based mediation mechanisms to resolve inheritance disputes.